Technology Acceptance Model (TAM) methodology system analysis on mobile banking users - Fadillah Wira Hutomo (Journal of Earth Kingdom, 2023)
This study aims to determine the effect of using Bank BTN's M-Banking (PT. Bank Tabungan Negara (Persero) Tbk) using the Modified TAM Method. The data collection used was by distributing electronic questionnaires to 436 respondents. This research method is quantitative research. The population in this study are Bank BTN M-Banking users who are domiciled in Jabodetabek, Central Java, East Java and Non Jabodetabek, Central Java and East Java, aged 17-50 years. The sample is determined using the Slovin formula. The research tests carried out were Validity Test, Reliability Test, Inner Model Test, Outer Model Test, and Path Coefficient Bootstrapping Test. Based on the results of data analysis, it can be concluded that Perceived Usefulness (XI), Perceived Ease of Use, Perceived Safety (X3), Perceived Credibility (X4), and Perceived Convenience (X5) have a significant influence on Consumer Usage of Mobile Banking (Y).